Deaf Cognition 2008
DOI: 10.1093/acprof:oso/9780195368673.003.0001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Underpinnings of Learning by Deaf and Hard-of-Hearing Students

Abstract: In recent years, the intersection of cognitive psychology, developmental psychology, and special populations has received increasing attention from a variety of academic and educational audiences (e.g., Baron-Cohen, Tager-Flusberg, & Cohen, 2000; Florian, 2007; Marschark & Spencer, 2003). Both research and pedagogy associated with this nexus have been motivated by the awareness of large individual differences as well as international differences in educational attainment. Among the latter (presumably cultural)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 58 publications
2
24
0
11
Order By: Relevance
“…Using similar data from a 30-year period, Qi and Mitchell (2007) reported that median mathematics achievement scores had not changed significantly over that time. The primary reasons that have been proposed to account for these results are a relative lack of early experiences with quantitative concepts (Bull 2008), delays in language development (Gregory 1998), insufficient teaching qualifications and practices in the area of mathematics (Kelly, Lang, and Pagliaro 2003), and sensory-and language-based differences in the ways that children with and without hearing loss process information (Marschark and Hauser 2008). Again, these are the knowledge, cognitive, and teaching issues identified by Spencer and Marschark (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Using similar data from a 30-year period, Qi and Mitchell (2007) reported that median mathematics achievement scores had not changed significantly over that time. The primary reasons that have been proposed to account for these results are a relative lack of early experiences with quantitative concepts (Bull 2008), delays in language development (Gregory 1998), insufficient teaching qualifications and practices in the area of mathematics (Kelly, Lang, and Pagliaro 2003), and sensory-and language-based differences in the ways that children with and without hearing loss process information (Marschark and Hauser 2008). Again, these are the knowledge, cognitive, and teaching issues identified by Spencer and Marschark (2010).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, in general, deaf students lag behind their hearing peers in relation to performance on mathematical tasks (see, e.g., Kelly, 2008). It is important to stress that there is a great heterogeneity amongst deaf learners, related to factors such as degree of hearing loss, use of devices such as hearing aids or cochlear implants, access (or not) at an early age to sign language (Marschark and Hauser, 2008). This makes generalisation difficult and the need to take into account the particularities of the students involved in any particular intervention paramount.…”
Section: Experiencing Mathematics Through Different Sensesmentioning
confidence: 99%
“…And it necessitates the development of new classroom cultures. Marschark and Hauser (2008) remind us of the Chinese proverb which tells us that a journey of 1,000 miles begins with a single step. The steps we are taking are very small, but we have started to walk.…”
Section: Legitimising Technology Use?mentioning
confidence: 99%
“…L'âge d'exposition à la LSF : les enfants nés de parents Sourds (enfants signeurs natifs) devraient obtenir de meilleures performances que les enfants nés de parents entendants non-signeurs (enfants soit signeurs tardifs, soit oralistes, cf. Schick 2006, Marschark & Hauser 2008. Notons cependant qu'en pratique de nombreuses régions en France n'offrent tout simplement pas la possibilité aux familles d'enfants sourds de suivre une scolarité en langue des signes et les contraignent à placer leur enfant en école oralisante 10 (ou à déménager).…”
Section: 22unclassified
“…Notons que d'autres variables peuvent intervenir dans le développement du langage et le développement cognitif, en relation avec le type d'établissement scolaire, à savoir la scolarisation en internat ou externat, même si les recherches récentes ne montrent pas d'effet, à long terme, du type d'établissement sur ce dé-veloppement (voir Marschark & Hauser 2008). 13 On citera ici Bernard Mottez (1990 ;2006 : 171-172) qui a très clairement présenté la situation :…”
unclassified